PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Hana Nadia Karimah; Eindye Taufiq (UNIVED Press, 2016)
Hana Nadia Karimah, Eindye Taufiq; This study is performed to examine the effect of short run tax avoidance, long run tax avoidance and firm value in companies go public of consumer goods industry in Indonesia Stock Exchange over period 1998 – 2013. The population of this research is 30 in companies go public consumer goods industry in Indonesia Stock Exchange over period 1998 – 2013. The data is obtained based on corporate finance reporting that at publication. It is gained sample amount of 8 consumer goods industry companies. The analysis technique used here is path analysis and hypothesis test using t-statistic with level of significant 5%. This research result that short run tax avoidance significantly effect on long run tax avoidance and research result that long run tax avoidance not significant to firm value.Keywords: Long Tax Avoidance, Short Tax Avoidance And Firm Value